Impact of Perceived Experiential Advertising on Consumer Behavior in Nepal: Evidence from S-O-R Theory (Quest Journal of Management and Social Sciences, 2024)
Background: Advertising styles have evolved, with experiential or engagement-based advertising emerging as a future trend. But, how different dimensions of experiential advertising impact brand credibility and consumer behavior in Kathmandu Valley is not examine so far.Objective: The study aims to assess the causal relationships between the influence of experiential advertising dimensions on brand credibility and consumer behavior, using the Stimulus-Organism-Response (S-O-R) theory as a framework.Method: An exploratory research design was employed, guided by the S-O-R theory. Data were collected through a survey administered using KOBO Toolbox and a structured questionnaire. Structural Equation Modeling (SEM) was used to analyze the data and explore the relationships between perceived experiential advertising, brand credibility, and consumer behavior.Result: The study finds that brand credibility mediates the relationship between perceived related, cognitive, and behavioral experiences and consumer behavior. SEM analysis reveals that related and behavioral advertising significantly impact brand credibility. Additionally, both related and behavioral advertising, as well as brand credibility, are significant predictors of consumer behavior. These results confirm the theoretical relevance of the S-O-R theory in the context of experiential advertising.Conclusion: Experiential advertising, particularly related and behavioral experiences, significantly impacts brand credibility and consumer behavior in Nepal. The findings suggest that organizations can benefit from focusing on these dimensions to build and maintain strong consumer relationships, enhancing long-term engagement and loyalty.Paper Types: Research PaperKeywords: Banking sector, brand credibility, consumer behavior, experiential advertising, SEMJEL Classification: M37, C12, D91, H1